Defining Boundaries in al-Andalus : Muslims, Christians, and Jews in Islamic Iberia - Safran, Janina M. (Book collections on Project MUSE., 2013)
Al-Andalus, the Arabic name for the medieval Islamic state in Iberia, endured for over 750 years following the Arab and Berber conquest of Hispania in 711. While the popular perception of al-Andalus is that of a land of religious tolerance and cultural cooperation, the fact is that we know relatively little about how Muslims governed Christians and Jews in al-Andalus and about social relations among Muslims, Christians, and Jews. This book takes a close look at the structure and practice of Muslim political and legal-religious authority and offers a rare look at intercommunal life in Iberia during the first three centuries of Islamic rule. The author makes creative use of a body of evidence that until now has gone largely untapped by historians - the writings and opinions of Andalusi and Maghribi jurists during the Umayyad dynasty. These sources enable her to bring to life a society undergoing dramatic transformation. Obvious differences between conquerors and conquered and Muslims and non-Muslims became blurred over time by transculturation, intermarriage, and conversion. The author examines ample evidence of intimate contact between individuals of different religious communities and of legal-juridical accommodation to develop an argument about how legal-religious authorities interpreted the social contract between the Muslim regime and the Christian and Jewish populations. Providing a variety of examples of boundary-testing and negotiation and bringing judges, jurists, and their legal opinions and texts into the narrative of Andalusi history, this book deepens our understanding of the politics of Umayyad rule, makes Islamic law tangibly social, and renders intercommunal relations vividly personal.